Survey of physician and pharmacist steward perceptions of their antibiotic stewardship programs - Shana A. B. Burrowes; Mari-Lynn Drainoni; Maria Tjilos; Jorie M. Butler; Laura J. Damschroder; Matthew Bidwell Goetz; Karl Madaras-Kelly; Caitlin M. Reardon; Matthew H. Samore; Jincheng Shen; Edward Stenehjem; Yue Zhang; et al. (Cambridge University Press, 2021)
Abstract Objective: To examine how individual steward characteristics (eg, steward role, sex, and specialized training) are associated with their views of antimicrobial stewardship program (ASP) implementation at their institution. Design: Descriptive survey from a mixed-methods study. Setting: Two large national healthcare systems; the Veterans' Health Administration (VA) (n = 134 hospitals) and Intermountain Healthcare (IHC; n = 20 hospitals). Participants: We sent the survey to 329 antibiotic stewards serving in 154 hospitals; 152 were physicians and 177 were pharmacists. In total, 118 pharmacists and 64 physicians from 126 hospitals responded. Methods: The survey was grounded in constructs of the Consolidated Framework for Implementation Research, and it assessed stewards' views on the development and implementation of antibiotic stewardship programs (ASPs) at their institutions We then examined differences in stewards' views by demographic factors. Results: Regardless of individual factors, stewards agreed that the ASP added value to their institution and was advantageous to patient care. Stewards also reported high levels of collegiality and self-efficacy. Stewards who had specialized training or those volunteered for the role were less likely to think that the ASP was implemented due to a mandate. Similarly volunteers and those with specialized training felt that they had authority in the antibiotic decisions made in their facility. Conclusions: Given the importance of ASPs, it may be beneficial for healthcare institutions to recruit and train individuals with a true interest in stewardship.